Impact of statin use on breast cancer recurrence and mortality before and after diagnosis: a systematic review and meta-analysis - Jia, Xiaolin; Lu, Ye; Xu, Zili; Mu, Qingqing (Frontiers in Oncology, 2023)
Objective: Breast cancer is one of the most common causes of death among women. Statins, typically used for cholesterol management, have been hypothesized to reduce recurrence and mortality rates in breast cancer. However, this association remains a subject of debate. This study evaluates the potential impact of statins on breast cancer recurrence and mortality. Methods: A comprehensive search was conducted in the PubMed, EMBASE, and Cochrane databases for articles published up to June 2023. These articles examined the effect of statins on breast cancer recurrence and mortality both before and after diagnosis. The analysis was performed using random-effects models, calculating pooled hazard ratios (HR) and their 95% confidence intervals (CI). Results: A total of 31 cohort studies, involving 261,014 female breast cancer patients, were included in this analysis. It was found that statin use prior to diagnosis was associated with a decrease in overall mortality (HR, 0.8; 95% CI, 0.69–0.93; I2 = 77.6%; P = 0.004) and breast cancer-specific mortality (HR, 0.76; 95% CI, 0.67–0.87; I2 = 72.7%; P < 0.001). Additionally, statin use after diagnosis was observed to reduce the recurrence of breast cancer (HR, 0.71; 95% CI, 0.61–0.82; I2 = 62%; P = 0.003), overall mortality (HR, 0.81; 95% CI, 0.70–0.92; I2 = 80.7%; P < 0.001), and breast cancer-specific mortality (HR, 0.76; 95% CI, 0.67–0.86; I2 = 74.5%; P < 0.001). Conclusions: The findings of this study indicate that statin usage, both before and after breast cancer diagnosis, may be associated with reduced risks of overall and breast cancer-specific mortality, as well as lower recurrence rates.